1997
DOI: 10.1046/j.1365-2591.1997.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of microbial coronal leakage in the restored pulp chamber of root‐canal treated multirooted teeth

Abstract: Summary This in vitro study investigated the effect of a resinreinforced glass ionomer lining material on the coronal leakage of a mixed obligate microbial marker in maxillary molars obturated with lateral condensation of cold gutta‐percha and Tubliseal sealer, after 2 years' storage. Forty maxillary first molars were prepared chemomechanically to a size 30–40 master apical file. The teeth were divided into an experimental group (30 teeth) and control group (10 teeth). In the experimental group, the floor of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
0
27
0
4
Order By: Relevance
“…In this study, the turbidity of the culture medium was used as reference and an indicator of microbial microleakage (a qualitative microbial analyze than quantitative). Chailertvanitkul et al (19) reported that in one qualitative analyze the microleakage is evidenced as positive only when occurred the turbidity on culture medium, indicating complete penetration of microorganisms through the restorative and root canal filling materials. Considering identical explanation, they reported that the number of microorganisms required to cause apical periodontitis until is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the turbidity of the culture medium was used as reference and an indicator of microbial microleakage (a qualitative microbial analyze than quantitative). Chailertvanitkul et al (19) reported that in one qualitative analyze the microleakage is evidenced as positive only when occurred the turbidity on culture medium, indicating complete penetration of microorganisms through the restorative and root canal filling materials. Considering identical explanation, they reported that the number of microorganisms required to cause apical periodontitis until is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…First, the apical seal may be affected adversely and cause the root canal treatment to fail. Second, movement of microorganisms and toxins through accessory canals in the floor of the pulp chamber may result in periodontal furcation involvement (39).…”
Section: Bacteria and Toxin Infiltration Methodsmentioning
confidence: 99%
“…If only one bacterium passes through the obturated root canal, it may multiply in the enriched broth and cause turbidity (38,39).…”
Section: Bacteria and Toxin Infiltration Methodsmentioning
confidence: 99%
“…However, those bacterial studies have been qualitative rather than quantitative. If only one bacterium passes through the obturated root canal, it may multiply in the enriched broth and cause turbidity 37,38) . The use of bacteria to assess coronal leakage also has its limitation because some of sealing materials have antibacterial activities 39) .…”
Section: Discussionmentioning
confidence: 99%